“A festa que é a mesma, sendo continuamente outra”: A ressignificação da Festa (do pau da bandeira) de Santo Antônio de Barbalha Ceará através das mudanças e continuidades. - Santos, Ruth Rodrigues (2015)
The party is a social phenomenon that allows multiple interpretations, this multiplicity comes from the diversity of the elements that articulates and composes, whether culture, religion, the individual and collective identity, symbols, rituals, fun (from playfulness) , politics, economy, tourism, etc. It is a temporal phenomenon, since it identifies the party time and space also because the party places (the street, the square, the house, the church, the religious community, etc.) express beyond the consensus, the tensions and conflicts. This set of elements becomes a rich field to analyze the interactions between individuals as "social actors". Considering its social and cultural vitality is that we propose to analyze the Feast of St. Anthony of Stick of Flag, held annually in the city of Barbalha, Ceara State, which includes the June festivities and expressions of popular religiosity site. I propose to reflect on the party dynamics, expressed in an extraordinary time, which articulates relations and ways of interactions between individuals and groups involved in the expectation processes, preparation and holding of the party in order to identify how changes and continuities contribute to its constant achievement. We show that the continuation of the festival is by renewal of interest and participation of individuals, which in turn is renewed, so reframe the party, that being the same, is continuously another.